If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(8 + -1x) = ln(3x + -2) + ln(x + 2) (8 * ln + -1x * ln) = ln(3x + -2) + ln(x + 2) (8ln + -1lnx) = ln(3x + -2) + ln(x + 2) Reorder the terms: 8ln + -1lnx = ln(-2 + 3x) + ln(x + 2) 8ln + -1lnx = (-2 * ln + 3x * ln) + ln(x + 2) 8ln + -1lnx = (-2ln + 3lnx) + ln(x + 2) Reorder the terms: 8ln + -1lnx = -2ln + 3lnx + ln(2 + x) 8ln + -1lnx = -2ln + 3lnx + (2 * ln + x * ln) 8ln + -1lnx = -2ln + 3lnx + (2ln + lnx) Reorder the terms: 8ln + -1lnx = -2ln + 2ln + 3lnx + lnx Combine like terms: -2ln + 2ln = 0 8ln + -1lnx = 0 + 3lnx + lnx 8ln + -1lnx = 3lnx + lnx Combine like terms: 3lnx + lnx = 4lnx 8ln + -1lnx = 4lnx Solving 8ln + -1lnx = 4lnx Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-4lnx' to each side of the equation. 8ln + -1lnx + -4lnx = 4lnx + -4lnx Combine like terms: -1lnx + -4lnx = -5lnx 8ln + -5lnx = 4lnx + -4lnx Combine like terms: 4lnx + -4lnx = 0 8ln + -5lnx = 0 Factor out the Greatest Common Factor (GCF), 'ln'. ln(8 + -5x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(8 + -5x)' equal to zero and attempt to solve: Simplifying 8 + -5x = 0 Solving 8 + -5x = 0 Move all terms containing l to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -5x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -5x = 0 + -8 -5x = 0 + -8 Combine like terms: 0 + -8 = -8 -5x = -8 Add '5x' to each side of the equation. -5x + 5x = -8 + 5x Combine like terms: -5x + 5x = 0 0 = -8 + 5x Simplifying 0 = -8 + 5x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -6z+8=-13 | | y=.66x-1.25 | | 1.5y-12=60 | | ln(8-x)=ln(3x-2)+ln(x-2) | | 8(3x-19)=15x+7 | | .5(4x+1)(3x)=27 | | -m+2n=3 | | 4-10.00+4=44 | | 0.04c=5 | | 3-2y=-8 | | 5r^2-44r+120=-50+11r | | -x+7=-13 | | 16-a=-14 | | 11=15t+5t^2 | | x+ay=byequals | | 2x^5-162=0 | | 8h^2-18hj-5j^2= | | 1.5y-12*4=180 | | (11+5v)-(13v+2)= | | 8-1x+4x=2-3x | | 17+2(2n-12)=1 | | -6m+4=2 | | -2+3(-1)=-(-1+6) | | -10y+18=-(5y-7)+6y | | 12*-3.8-10=4*-3.8-32-3*-3.8 | | 16-8n+3+2n=45 | | 2x+7=6x-14 | | .5x-2=8 | | 9m-15=66 | | 4(2p-2)=3(2p+4) | | -3(2-1x)=2x-9 | | 2=-2y+6/13 |